Electrical Conduction at the Interface between Insulating van der Waals Materials. (6th March 2019) - Kashiwabara, Yuta; Nakano, Masaki; Nakagawa, Yuji; Wang, Yue; Matsuoka, Hideki; Iwasa, Yoshihiro
Abstract: Emergent properties of 2D materials attract considerable interest in condensed matter physics and materials science due to their distinguished features that are missing in their bulk counterparts. A mainstream in this research field is to broaden the scope of material to expand the horizons of the research area, while developing functional interfaces between different 2D materials is another indispensable research direction. Here, the emergence of electrical conduction at the interface between insulating 2D materials is demonstrated. A new class of van der Waals heterostructures consisting of two sets of insulating transition‐metal dichalcogenides, group‐VI WSe2 and group‐IV TM Se2 ( TM = Zr, Hf), is developed via molecular‐beam epitaxy, and it is found that those heterostructures are highly conducting although all the constituent materials are highly insulating. The WSe2 /ZrSe2 interface exhibits more conducting behavior than the WSe2 /HfSe2 interface, which can be understood by considering the band alignments between constituent materials. Moreover, by increasing Se flux during heterostructure fabrication, the WSe2 /ZrSe2 interface becomes more conducting, reaching nearly metallic behavior. Further improvement of the crystalline quality as well as exploring different material combinations are expected to lead to metallic conduction, providing a novel functionality emerging at van der Waals heterostructures. Abstract : Highly conducting interfaces between insulating 2D materials are demonstrated in van der Waals heterostructures fabricated by molecular‐beam epitaxy. In situ growth monitoring by reflection high energy electron diffraction confirms layer‐by‐layer fabrication of the heterostructures and the formation of abrupt interfaces. Hall effect measurements reveal that the conducting carriers are holes, and their densities are as large as 10 14 cm −2 .